Maintaining and disrupting global-North hegemony/global-South dependence in a local African sport for development organisation: the role of institutional work. Issue 3 (3rd July 2019) - McSweeney, Mitchell; Kikulis, Lisa; Thibault, Lucie; Hayhurst, Lyndsay; van Ingen, Cathy
ABSTRACT: Recently, conceptual developments in the field of institutional theory, such as institutional work, that refer to the practices and processes of individuals and organisations aimed at creating, maintaining and disrupting institutions, have emphasised how institutions are engaged in and affected by organisational actors. Institutions and humans are in a recursive relationship, whereby humans both shape and are shaped by institutional templates through political processes infused with power dynamics. In this paper, research conducted in a local African sport for development (SFD) organisation is featured. SFD is a field of increasing institutionalisation in policy and practice. This study underscores the valuable utilisation of institutional work for exploring international development and sport policy and practice. Using an ethnographic approach, how organisational actors at a local SFD site in a community in sub-Saharan Africa influenced the institutionalised nature of SFD was examined. We provide specific details about the features of the micro-processes of symbolic and relational work in maintaining and disrupting the institution of SFD and discuss three sub-themes in relation to global North hegemony/global South dependence: (1) health awareness, (2) social development and (3) sport development. Future studies of sport in general and SFD in particular would be well-suited to adopt an institutional work perspective in order for in-depth understandings of local relations, international policy and organisational actors and institutions. Abbreviations: SFD: sport for development; NGOs: non-governmental organisations; IOC: International Olympic Committee; NCAA: National Collegiate Athletic Association; NSA: National Sports Association; SC: Sports Centre; CSA: Canadian Sport Association; UN: United Nations; ODR: Olympic Day Run